49 Prevalence and predictors of qtc prolongation in acute medical admissions. (5th October 2017) - Coughlan, JJ; Fitzgerald, G; Wafer, M; MacDonnell, C; Liston, R
Abstract : Introduction: An ECG is commonly performed at the point of medical admission. Amongst the myriad of information provided by an ECG, the QT interval is often overlooked and is a risk factor for ventricular arrhythmias. We sought to determine the prevalence of QTc prolongation amongst patients admitted to hospital on acute medical take and to determine if there was a relationship between this, electrolyte abnormalities and drugs known to prolong the QT. Methods: Prospective observational study, analysing the clinical notes of >100 consecutive patients admitted to our centre. The primary outcome to be assessed was the prevalence of a prolonged QTc. Secondary outcomes were: (1) Degree of QTc prolongation (2) Presence of QTc prolonging medications on admission (3) Initiation of QTc prolonging medications after admission (4) Presence of Electrolyte abnormalities associated with QTc prolongation Chi squared test was used to compare categorical data. Students t test was used to compare means between groups. Results: 26% of all patients admitted had a QTc above the traditional normal range of 440 ms. 14% of patients had a QTc in the practically prolonged category as per AHA guidelines (>450 ms for men, >460 ms for women) and 2% of patients had a QTc in the very prolonged range (>500 ms). No patients had documentation of their QTc in their medical admission note, despite our pro-forma medical admission note template having a section specifically for ECG findings. Nearly half of all admitted patients (47%) were taking at least one medication known to prolong the QTc prior to their admission. 29.78% of these patients were then prescribed a further medication known to prolong the QT interval. 8 of these patients had a QTc >460 ms. A higher proportion of patients with QTc >440 ms were on drugs known to prolong the QTc than patients with normal QTc but this did not reach statistical significance (61.5% vs 42.5%, p=0.0945). Overall, 24% of all admitted patients were started on at least one medication associated with prolongation of the QTc. Of the patients with prolonged QTc at baseline, 34.6% were started on a medication known to prolong the QTc. Electrolyte abnormalities associated with QTc prolongation were also measured in our cohort. Of these only serum K+ was found to be statistically significantly lower in the prolonged QTc group (Mean 3.28 mmol/L vs. 3.98 mmol/L, p=0.0077). Serum Magnesium (p=0.1193) or Calcium (p=0.1443) levels were numerically but not statistically significantly lower in the prolonged QTc group. Conclusion(s): QTc prolongation is common amongst acute medical admissions in the Irish setting. A high proportion of medical admissions are already on medications known to prolong the QTc. We would recommend screening for QTc prolongation in all patients admitted on medical take.